Effect of Vitamin D Supplementation on C-reactive Protein in Patients with Nonalcoholic Fatty Liver - Foroughi, Mahdi (Int J Prev Med, 2014)
BACKGROUND: Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease in the worldwide. It is associated with chronic disorders such as diabetes and heart diseases. Inflammation is one of the basic causes of metabolic diseases. Several studies have shown that Vitamin D can reduce inflammation. The purpose of this study was to investigate the effect of Vitamin D supplementation on inflammation in patients with NAFLD. METHODS: This study involved 60 NAFLD patients, divided equally into two intervention and placebo groups. During 10 weeks, patients in the intervention group receive Vitamin D (capsules containing 50,000 IU vitamin D), weekly. Vitamin D levels, C-reactive protein (CRP), triglyceride (TG), aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels were measured at the beginning and end of the study. Data were analyzed using analysis of covariance tests. Analyses were done using SPSS software (version 16) (SPSS Inc., Chicago, USA). P < 0.05 set as significant level. RESULTS: Vitamin D supplementation resulted in an increase of serum 25(OH) D concentrations in inter group (P < 0.05) and intra-group (P < 0.05) in intervention group. At the end of the study, in the intervention group, TG and CRP reduced significantly compare with baseline (P < 0.05). A significant increase was seen in calcium serum in the intervention group in comparison with baseline (P < 0.05) and compared with the placebo group (P < 0.05). CONCLUSIONS: Vitamin D supplementation had no effect on CRP and other variables in the intervention group compared with the placebo group. Further studies with strong design and more sample must conduct to demonstrate the effect of Vitamin D supplementation on inflammation in patients with NAFLD.